Moiré patterns observed in bi layer graphene irradiated with high energetic protons - Galván, Donald H.; Posada Amarillas, A.; Mejía Rosales, Sergio; Wing, C.; Yacamán, Miguel José (Springer, 2014)
Customarily, it is likely that irradiated graphene yield indication of per- turbations induced by irradiation. High Resolution Transmission Electron Micros- copy (HRTEM) analysis has been performed on proton irradiated graphene. The analysis indicates the existence of Moiré patterns produced by the rotations induced by the irradiation in between planes. The rotations measured fluctuate between 3 and 5 degrees respectively. These rotations may influence the electronic properties of the material under investigation. In order to explain the observed rotations in between planes, theoretical analysis were performed under the scheme of extended Hückel tight-binding method. Average total energy of the system was careful ana- lyzed throughout the experiment composed of two graphene layers with two carbon vacancies and then the replaced carbons were intercalated in between the two lay- ers. The results obtained indicate that the system remain semi metallic. Moreover, the theoretical results yielded that the 3 degree rotation is favored, although the 5 degree rotation is not discarded. Furthermore, energy bands as well as total and projected DOS were performed in order to provide more information about the electronic changes induced by the rotations applied to the system.